COVID-19 Vaccine Acceptability Among People Experiencing Homelessness in Central Florida and Southern Nevada, March-June 2021. Issue 6 (8th November 2022) - Meehan, Ashley A.; Aarvig, Kathleen; Kashani, Mitra; Whitton, Alaina; Mosites, Emily
Abstract : Context: Understanding COVID-19 vaccine acceptability among people experiencing homelessness is critical to improve vaccine coverage during the COVID-19 pandemic. Little is known about COVID-19 vaccine acceptability people experiencing unsheltered homelessness (PEUH). Objective: To identify and describe motivators for receiving a COVID-19 vaccine and reasons for hesitancy, information sources utilized and trusted for vaccine decision making, logistical barriers to receiving vaccination, and what might increase comfortability to receive a COVID-19 vaccination among PEUH. Design: Cross-sectional survey design, implemented from March to June 2021. Setting: Two US cities: Las Vegas and Nevada (urban), and Orlando, Florida (suburban). Participants: People experiencing predominantly unsheltered homelessness accessing handwashing stations and other wrap-around social services at program sites managed by Clean the World Foundation. Main Outcome Measures: The main outcome measures assessed included survey responses about current vaccine receipt (if participants have already received one or more doses of a COVID-19 vaccine), intention to receive a COVID-19 vaccine if not already received, motivators for receiving or wanting to receive a vaccine, reasons for hesitancy or uncertainty about receiving a vaccine, sources of information regarding COVID-19 vaccines, and actual or anticipated logistical barriers or challenges to receiving COVID-19 vaccines. Results: Among 864 participants, 465 (53.8%) were classified as "vaccine accepting, " and 399 were classified "vaccine hesitant or undecided." The primary motivator to be vaccinated was to protect their health (212, 45.6%). Hesitant or undecided participants reported that vaccines were too new (269, 67.4%) or they needed more information (223, 55.9%) and were more likely to receive information from social media than accepting participants (80.0% vs 58.3%, P < .001). Logistical barriers to vaccination included distance to vaccination locations (85, 21.3%), lack of transportation (79, 19.8%), and limited time (64, 16%). Conclusions: Vaccination efforts to reach PEUH should consider how information and logistical needs may be addressed.